Disseminated Histoplasmosis in Persons Living with HIV, France and Overseas Territories,1992–2021 - Nacher, Mathieu; Marshall, Esaïe; Bani-Sadr, Firouze; Peugny, Sandrine; Denis, Blandine; Ouedraogo, Elise; Gallien, Sebastien; Meybeck, Agnes; Françoise, Ugo; Adenis, Antoine; Vignier, Nicolas; Couppié, Pierre; et al. (Emerging infectious diseases, 2025)
Disseminated histoplasmosis is a major issue among persons with advanced HIV in the Americas; it might also affect persons in sub-Saharan Africa, the Caribbean, and Asia and can be mistaken for other infections. By using 1992-2021 data from the French hospital database on HIV, we analyzed 198,798 persons with HIV follow-up in France and its overseas territories, identifying 553 (2.8/1,000 person-years) first episodes of disseminated histoplasmosis. Incidence rates varied by site of follow-up: 9.41 in French Guiana, 0.76 in Guadeloupe, 0.62 in Martinique, and 0.079 in mainland France. Incidence rates in France also varied between regions of origin or travel: 4.73 for Central or South America, 1.36 for the Caribbean, and 0.19 for sub-Saharan Africa or Asia. Differences persisted after adjusting for age, sex, CD4 count, and viral load at baseline. Overall, incidence and early death have declined, likely because of antiretroviral drug rollout in France.